2018
DOI: 10.1007/s00392-018-1204-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term outcome of focal atrial tachycardia ablation in the real world: results of the german ablation registry

Abstract: In this large patient population, FAT ablation had a relatively high acute success rate with a low complication rate. During follow-up, the recurrence rate was high, particularly in biatrial location. This was frequently predicted by an early recurrence during hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
1
25
0
3
Order By: Relevance
“…Some significant complications have been associated with catheter ablation of focal atrial tachycardia, including atrioventricular block, sinus node dysfunction, perforation, thrombus formation, pericardial effusion, phrenic nerve damage, thromboembolism, and cardiac arrest. [13][14][15] In our study, we did not encounter any permanent complications. One patient developed a second-degree atrioventricular block during ablation in the parahisian region.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Some significant complications have been associated with catheter ablation of focal atrial tachycardia, including atrioventricular block, sinus node dysfunction, perforation, thrombus formation, pericardial effusion, phrenic nerve damage, thromboembolism, and cardiac arrest. [13][14][15] In our study, we did not encounter any permanent complications. One patient developed a second-degree atrioventricular block during ablation in the parahisian region.…”
mentioning
confidence: 51%
“…Other studies also reported higher fluoroscopy times in children and adults with focal atrial tachycardia who underwent a transcatheter ablation using three-dimensional electroanatomic mapping. 3,4,13 The mean fluoroscopy time was as high as 40 ± 20 minutes in some studies even with the utilisation of a three-dimensional mapping system. 4 In our study, fluoroscopy was required only for the transseptal puncture in nine patients with left-sided foci.…”
mentioning
confidence: 99%
“…For focal ATs from the LA, acute success rates for ablation are about 85% . Recurrences are more common in patients who have multiple or biatrial foci.…”
Section: Outcomes After Ablating Left Atrial Tachycardiasmentioning
confidence: 99%
“…For focal ATs from the LA, acute success rates for ablation are about 85%. 51,52 Recurrences are more common in patients who have multiple or biatrial foci. In an earlier cohort of patients treated between 2007 and 2010, which preceded the introduction of contact force monitoring, arrhythmia freedom without antiarrhythmic drugs was 58%.…”
Section: Outcomes After Ablating Left Atrial Tachycardiasmentioning
confidence: 99%
See 1 more Smart Citation